Exposure to Genocide as a Risk Factor for Homicide Perpetration in Rwanda: A Population-Based Case–Control Study. Issue 12 (June 2018) - Rubanzana, Wilson; Hedt-Gauthier, Bethany L.; Ntaganira, Joseph; Freeman, Michael D.
A population-based case-control study was conducted to assess the relationship between genocide exposure and homicide perpetration in Rwanda. A sample of 150 homicide perpetrators who were charged with and confessed to having committed homicide between 1 May 2011 and 31 May 2013 and 450 controls were enrolled. Cases were matched to controls by neighborhood, age and sex. Socio-demographic, background and genocide-related information was collected from study subjects' next of kin. Four characteristics of genocide exposure were: genocide survivor, genocide perpetrator, having lost a first-degree relative to genocide and having a first-degree relative convicted of genocide. We assessed the impact of each genocide-exposure variable using conditional logistic regression. Of the 150 cases, 124 (82.7%) were male and 26 (17.3%) were female. The mean age of the alleged homicide perpetrators was 33 years, with a peak in the age group 20-29 years (39.3%). After adjusting for socio-demographic characteristics and past common criminal records, having a first-degree relative who had been convicted of genocide crimes was a significant predictor for homicide perpetration (odds ratio [OR] = 14.4, 95% confidence interval [CI] = 1.6-129.4). Being a genocide perpetrator, a genocide survivor and having lost a first-degree family member to genocide were not identified as risk factors for homicide perpetration. In Rwanda, young people who experienced early exposure to trauma by witnessing their first-degree relatives' active participation in the genocide, are more likely to commit homicide. Socio-economic and psychotherapeutic programs targeting this population group are needed to rehabilitate these young people for violent behavior change.